Hubungan Antara Tingkat Pendidikan, Pengetahuan dan Perilaku Ibu Terhadap Status Karies Pada Anak Usia Prasekolah di TK Laksmi, Kartasura, Kab. Sukoharjo Tahun 2014 - Purwaka, Dora Pratiwi; , Dwi Kurniawati, S.KG, MPH; , drg. Nilasary Rochmanita S, MDSc (2015)
Half of 75 millions children are known to have tooth decay and this number will increase continuosly. The incidence of caries in children so widely even it's based on age groups. Children 3 years of age by 40%, at 4 years of age by 55% and 5 years of age by 75%. Any factors that prevent caries status of children are mother's knowledge and behavior about oral health. Because dental care could be a basic of positive behavior to maintain healthy teeth and mouth. The aim of this study was to know the correlation between mother's education level, knowledge and behavior with dental caries status of preschool children. This study was carried on multiple linear regression analysis with total subjects 33 persons. Based on classic assumption test result that the variables didn't have multicorrelation problem and for heteroskesdasticity test showed no problem found on the model. Coefficient of determination value resulted from properness model test was 0,207 means that 20,7% variation of dependent variable can be explained by independent variable. T-test result showed that mother's knowledge variable has significant correlation with dental caries status of preschool children at 95% of significance level, while mother's education level and behavior did not